Protein disulfide-isomerase A3 knockdown attenuates oxidized low-density lipoprotein-induced oxidative stress, inflammation and endothelial dysfunction in human umbilical vein endothelial cells by downregulating activating transcription factor 2. Issue 1 (1st January 2022) - Jia, Jing; Wang, Yueping; Huang, Ruijuan; Du, Fengxia; Shen, Xiaozhu; Yang, Qiurong; Li, Juan
ABSTRACT: Atherosclerosis is a chronic inflammatory disease implicated in oxidative stress and endothelial dysfunction. Protein disulfide-isomerase A3 (PDIA3) has been reported to regulate oxidative stress and suppress inflammation. This study aimed to explore the function of PDIA3 in atherosclerosis and the underlying mechanisms. PDIA3 expression in oxidized low-density lipoprotein (ox-LDL)-induced human umbilical vein endothelial cells (HUVECs) was detected using RT-qPCR and Western blotting. Following PDIA3 knockdown through transfection with small interfering RNA targeting PDIA3, cell viability, oxidative stress and inflammation in ox-LDL-induced HUVECs was examined using a Cell Counting Kit-8, corresponding kits and ELISA, respectively. The levels of CD31, α-smooth muscle, iNOS, p-eNOS, eNOS and NO were assessed using RT-qPCR, Western blotting and an NO kit to reflect endothelial dysfunction in ox-LDL-induced HUVECs. The relationship between PDIA3 and the activating transcription factor 2 (ATF2) was confirmed using co-immunoprecipitation. In addition, ATF2 expression was examined following PDIA3 silencing. The results indicated that PDIA3 was highly expressed in ox-LDL-induced HUVECs. PDIA3 silencing increased cell viability, and reduced oxidative stress and inflammation, as evidenced by the decreased levels of reactive oxygen species, malondialdehyde, TNF-α, IL-1β and IL-6, and increased superoxide dismutase and glutathione peroxidase activity. In addition, PDIA3 deletion improved endothelial dysfunction. PDIA3 interacted with ATF2, and PDIA3 deletion downregulated ATF2 expression. Furthermore, ATF2 overexpression reversed the effects of PDIA3 knockdown on ox-LDL-induced damage of HUVECs. Collectively, PDIA3 knockdown was found to attenuate ox-LDL-induced oxidative stress, inflammation and endothelial dysfunction in HUVECs by downregulating ATF2 expression, showing promise for the future treatment of atherosclerosis.